Vasorelaxing Action of the Kynurenine Metabolite, Xanthurenic Acid: The Missing Link in Endotoxin-Induced Hypotension? - Carmine Vecchione; Carmine Vecchione; Francesco Fazio; Albino Carrizzo; Luana Lionetto; Antonio Damato; Luca Capocci; Mariateresa Ambrosio; Giuseppe Battaglia; Valeria Bruno; Valeria Bruno; Michele Madonna; et al. (Frontiers Media S.A., 2017)
The kynurenine pathway of tryptophan metabolism is activated by pro-inflammatory cytokines. L-kynurenine, an upstream metabolite of the pathway, acts as a putative endothelium-derived relaxing factor, and has been hypothesized to play a causative role in the pathophysiology of inflammation-induced hypotension. Here, we show that xanthurenic acid (XA), the transamination product of 3-hydroxykynurenine, is more efficacious than L-kynurenine in causing relaxation of a resistance artery, but fails to relax pre-contracted aortic rings. In the mesenteric artery, XA enhanced activating phosphorylation of endothelial nitric oxide synthase (NOS), and the relaxing action of XA was abrogated by pharmacological inhibition of NOS and endothelial-derived hyperpolarizing factor. Systemic injection of XA reduced blood pressure in mice, and serum levels of XA increased by several fold in response to a pulse with the endotoxin, lipopolysaccharide (LPS). LPS-induced hypotension in mice was prevented by pre-treatment with the kynurenine monooxygenase (KMO) inhibitor, Ro-618048, which lowered serum levels of XA but enhanced serum levels of L-kynurenine. UPF 648, another KMO inhibitor, could also abrogate LPS-induced hypotension. Our data identify XA as a novel vasoactive compound and suggest that formation of XA is a key event in the pathophysiology of inflammation-induced hypotension.